Honey-based mixtures used in home medicine by nonindigenous population of Misiones, Argentina - Kujawska, Monika (2012)
Honey-based mixtures used in home medicine by nonindigenous population of Misiones, Argentina. Medicinal mixtures are an underinvestigated issue in ethnomedical literature concerning Misiones, one of the most bioculturally diverse province of Argentina. The new culturally sensitive politics of the Provincial Health System is a response to cultural practices based on the medicinal use of plant and animal products in the home medicine of the local population. Honey-based medicinal formulas were investigated through interviews with 39 farmers of mixed cultural (Criollos) and Polish origins in northern Misiones. Fifty plant species and 8 animal products are employed in honey-based medicines. Plants are the most dominant and variable elements of mixtures. Most of the mixtures are food medicines. The role of honey in more than 90% of formulas is perceived as therapeutic. The ecological distribution of taxa and the cultural aspects of mixtures are discussed, particularly the European and American influences that have shaped the character of multispecies medicinal recipes.